The Critical Thinking Skills of Students Through Guided Inquiry Models in Elementary School - Nurul Fitriah Aras; Mardi Lestari; Sinta Satria Dewi Pendit; Nurul Kami Sani (Jurnal Studi Guru dan Pembelajaran, 2024)
The urgency of this research is driven by the deficiency in students' critical thinking skills, which is rooted in the dominance of lecture-based teaching approaches. These traditional methods restrict student engagement and exploration, crucial for fostering critical thought. The research aims to explore the impact of the guided inquiry learning model on enhancing critical thinking skills among elementary students, specifically focusing on a sample of 40 fifth-grade students at SDN Lonja. Utilizing a quasi-experimental design with pretest and posttest control groups, the study gathered data through tests, observations, and documentation. The Paired Samples Test used for data analysis indicated a significant difference at the 5% level, with a p-value of 0.000. This outcome led to the rejection of the null hypothesis, confirming that the guided inquiry model significantly enhances students' critical thinking skills in Natural Sciences. The findings underscore the potential of guided inquiry as an effective instructional model, which actively engages students in learning, promotes analytical thinking, and reduces dependency on rote memorization, thereby nurturing critical thinking competencies essential for lifelong learning and problem-solving. This research holds implications for educators and curriculum developers seeking to adopt student-centered learning strategies that better prepare students for future academic and personal challenges.